2015
DOI: 10.4067/s0717-95532015000100002
|View full text |Cite
|
Sign up to set email alerts
|

Control Emocional, Felicidad Subjetiva Y Satisfacción Vital Relacionados Al Afrontamiento Y Adaptación en Personas Con Cáncer Avanzado

Abstract: RESUMENLa teoría del Proceso de Afrontamiento y Adaptación de Roy identifica las estrategias que utiliza la persona para responder a las influencias y cambios ambientales que percibe, de manera de crear una integración humana y ambiental. El objetivo de esta investigación fue conocer la relación entre las variables individuales -control emocional, satisfacción vital y felicidad subjetiva-con el proceso de afrontamiento y adaptación al cáncer, en usuarios con diagnóstico de cáncer avanzado del Policlínico del D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
1
5
1
6
Order By: Relevance
“…Our findings also confirmed the studies that demonstrated that high levels of EA are not necessarily beneficial and that paying excessive attention to own emotional states can lead to negative psychiatric symptoms such as anxiety that can decrease WA. 24,25 Hence, higher EA levels might act as a comorbidity factor that might lead to ruminative thoughts undermining WA. 27 Our results also showed that age decreased WA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also confirmed the studies that demonstrated that high levels of EA are not necessarily beneficial and that paying excessive attention to own emotional states can lead to negative psychiatric symptoms such as anxiety that can decrease WA. 24,25 Hence, higher EA levels might act as a comorbidity factor that might lead to ruminative thoughts undermining WA. 27 Our results also showed that age decreased WA levels.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The importance of PEI as a covitality factor increasing well-being, quality of life, and adaptation has also been deeply investigated in BC patients. 24,25 However, studies have shown different empirical results depending on the PEI dimension evaluated. While some studies suggested a negative relationship between EA, anxiety, and depression in undergraduate students, 26 other authors have found a positive association between EA and anxiety, suggesting that high EA is not necessarily beneficial.…”
mentioning
confidence: 99%
“…Studies focused on emotional intelligence generally address this construct as a protective factor in health, suggesting that the way that breast cancer women regulate their emotions influences their quality of life and enhance disease adaptation (Hermosilla-Ávila and Sanhueza-Alvarado, 2015;Brandão et al, 2016;Amirifard et al, 2017;Baudry et al, 2018). Besides, some studies show how emotional intelligence predicts changes in psychological, social and physical well-being, satisfaction, optimism, social adjustment and the quality of interpersonal relationships, as well as in post-traumatic growth in breast cancer women (Rey et al, 2013;Mahdavi et al, 2015;Ahoiee et al, 2017;Rider Mundey et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nuestra propia revisión basada en artículos científicos sobre la temática del BS en Chile en los últimos cinco años nos permitió observar un claro énfasis en la dimensión hedónica y un vacío de conocimiento en la medición del componente eudamónico. Estudios que relacionan el BS con el estado de salud personal utilizan el nivel de satisfacción y felicidad global con la vida como indicadores del BS (Denegri et al, 2016;Fernández Lorca & Lay, 2020;Hermosilla Ávila & Sanhueza Alvarado, 2015;Lobos et al;2015;Oyanedel, Alfaro, & Mella, 2015;Sánchez et al, 2017;Schnettler et al, 2016;. Otros enfocados en evaluar desigualdades en el bienestar subjetivo según territorio (Vargas et al, 2016) y género (Boncompte & Paredes, 2020) también utilizan la satisfacción con la vida como indicador principal.…”
Section: Las Limitaciones En La Investigación Del Bs En Chileunclassified